Consumers in the Circular Economy: Attitude towards Products and Factors Affecting Intention to Purchase Circular Fashion Products of Generation Y (Millennials) in Bangkok - Kayom, Watcharaporn; Hongkanak, Supawadee (Rajapark Journal, 2024)
This research aimed to study the influence of personal norms, environmental knowledge, perceived government policy, and attitudes towards products that affect the intention to purchase circular fashion products of Generation Y (Millennials) in Bangkok. Quantitative research was applied in this research. Data were collected using questionnaires from Generation Y (Millennials) consumers in Bangkok. A sample size of 345 people was analyzed using descriptive statistics, and structural equation modeling (SEM) was performed to test research hypotheses. The results found that 1) the level of the personal norm, environmental knowledge, perceived government policy, attitude towards products, and intention to purchase circular fashion products are at a high level; 2) the personal norm, environmental knowledge, and perceived government policy have a positive influence on attitude towards products; 3) attitude towards products has a positive influence on the intention to purchase circular fashion products; 4) the factor that influences the intention to purchase circular fashion products is an attitude towards products. It has a direct influence equal to 0.915, while the highest indirect influence is perceived government policy equal to 0.296. 5) The structural equation model is congruent with the empirical data. All passed the acceptance criteria (c2 equal to 59.025, df equal to 53, c2/df equal to 1.114, p-value equal to 0.265, RMSEA equal to 0.018, CFI equal to 0.999, TLI equal to 0.995, and SRMR equal to 0.025), and 6) with the cooperation of both government sectors, business sectors, and consumers, the research gained new knowledge on the consumer model in the circular economy. It can promote the intention to purchase circular fashion products by developing personal norms, environmental knowledge, perceived government policy, and consumer attitudes toward products.